Efektifitas Socrative untuk Assesmen Diagnostik Gaya Belajar Siswa Madrasah Ibtidaiyah - Ahmad Syaifuddin (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2024)
To maximize the results and learning process, it is necessary to map student learning styles as a preference for teachers to prepare appropriate learning plans. Mapping student learning styles is carried out by carrying out formative test activities. This research is descriptive qualitative. In this research, the assessment given was in the form of a questionnaire. Students are given a number of questionnaires via the Socrative web-based application. This test was carried out to map the learning styles of class 6 A students at MI Mamba'ul Ulum Dagan TP. 2022/2023. From the results, it can be concluded that the tendency of students' learning style in class 6 A is an auditory learning style. This conclusion is based on the percentage of interpretation of the results of the money questionnaire given, namely 36.7% have an auditory learning style, 33.3% have a visual learning style, 20% have a kinesthetic learning style, 6.7% have a combined auditory and visual learning style and 3.3% have kinesthetic and visual learning styles. These results indicate that Socrative is effective for diagnostic assessment of student learning styles. Untuk dapat memaksimalkan hasil serta proses pembelajaran perlu dilaksakan pemetaan tentang gaya belajar siswa sebagai preferensi bagi guru menyusun perencanaan pembelajaran yang tepat. Pemetaan gaya belajar siswa dilakukan dengan melaksanakan kegiatan tes formatif. Penelitian ini adalah deskriptif kualitatif. Dalam penelitian ini asesmen yang diberikan berbentuk quesioner. Siswa diberikan sejumlah quesioner melalui aplikasi berbasis web socrative. Tes ini dilakukan untuk memetakan gaya belajar siswa kelas 6 A MI Mamba’ul Ulum Dagan TP. 2022/2023. Hasilnya bisa diambil kesimpulan bahwasannya kecenderungan gaya belajar siswa di kelas 6 A adalah gaya belaja auditori. Kesimpulan ini berdasarkan persentase hasil interpretasi hasil isian questioner uang diberikan yaitu 36,7% gaya belajar auditori, 33,3% memiliki gaya belajar visual, 20% memiliki gaya belajar kinestetik, 6,7% memiliki gaya belajar gabungan auditori dan visual dan 3,3% memiliki gaya belajar kinestetik dan visual. Hasil ini menunjukkan bahwa Socrative efektif untuk assesmen diagnostik gaya belajar siswa.